Plasma mineral profile in relation to pregnancy rate in repeat breeding cows - PRASAD, J K; SINGH, BERENDRA; GUPTA, H P; KUMAR, MAHESH (The Indian Journal of Animal Reproduction, 2007)
Thirty eight crossbred cows were taken with the history of repeat breeding condition to study the plasma mineral profile viz. copper (Cu), cobalt (Co), zinc (Zn), magnesium (Mg) and calcium (Ca) in relation to pregnancy rate. The percentage of aninlals significantly deficient in plasma level of Cu, Co, Zn, Mg and Ca were 34.21%, 21.05%, 44.74%, 42.10% and 26.32%, respectively. All the animals were inseminated in the subsequent estrus and pregnancy rate was confirmed by palpation per-rectum. The pregnancy was significantly lower in the animals deficient in Cu (64.00% in normal cows’ vs 7.70% in deficient cows) and Zn (57.00% in normal cows’ vs 23.53% in deficient. cows). The present study clearly indicates that minerals viz. Cu, Co, Zn, Mg and Ca are essential for optimum fertility; however, deficiency of Cu and Zn plays a significant role in reducing the conception rate.